Shrimp cephalothorax meal in laying hen diets: effects on egg. - Chacón-Villalobos, Alejandro (2015)
The aim of this study was to evaluate the effect of shrimp cephalothorax meal Pleuroncodes planipes (HC) in laying hen diets over egg quality and yolk color. From April to September 2013 in San José Costa Rica, four inclusion levels of meal were evaluated (0% HC, 5% HC, 10% HC, 15% HC) in rations for 140 Hy-Line Brown hens (35 per treatment). There were no significant differences (p>0.05) for Haugh units (M= 90), yolk index (M= 0.41), and pH (M= 6.2). The lowest shell thickness was for 15% HC (M= 0.44 mm) (p<0.05). The morphological index differed (p<0.05) between 15 % HC (M = 77.04%) and 0% HC (M = 76.23%). Weight was different (p<0.05) for 5% HC (M= 62.76 g) and 10% HC (61.43 g). Roche color value was higher (p<0.05) for 15% HC (M= 14). There were no differences (p>0.05) among color parameters L* (M= 61.59), b* (M= 57.58) and C* (M = 62.60). The parameter a* was significantly higher (M=72,4) (p<0.05) for 15% HC (M= 29.34). The °h parameter was higher for 0% HC (p<0.05) (M=72.39), and liking for the color of yolk (M= 7.4) was higher as well (p<0.05). Flavor liking generated three clusters: 40% of people preferred 0% HC, 27% preferred 15% HC, and 33% were indifferent. The results show that the inclusions of HC are associated with an acceptable liking of egg, generating a possible market to produce them with inclusions among 10% and 15% HC.